The Effect of Reciprocal Teaching and Self-Concept upon the Reading Comprehension of the Tenth Grade Students of SMA Negeri 1 Gianyar. Thesis. Language Education Study Program, Postgraduate Program, Ganesha University of Education. - Maharani, Anak Agung Putri (Jurnal Pendidikan Bahasa, 2012)
Maharani, Anak Agung Putri (2012), The Effect of Reciprocal Teaching and Self-Concept upon the Reading Comprehension of the Tenth Grade Students of SMA Negeri 1 Gianyar. Thesis. Language Education Study Program, Postgraduate Program, Ganesha University of Education.This thesis has been approved and corrected by:Supervisor IÂ Â Â : Prof.Dr. A.A. Istri Ngurah Marhaeni, M.A. Supervisor IIÂ Â Â : Dra. Luh Putu Artini, M.A., Ph.D.Keywords: reading comprehension, reciprocal teaching, self-concept. This study aimed at: a) investigating the significant difference in reading comprehension between the students who are taught by using reciprocal teaching and those who are taught by using conventional teaching; b) investigating the interactional effect between teaching methods and self-concept upon studentsâ reading comprehension; c) investigating the significant difference in reading comprehension between the students with high self-concept who are taught by reciprocal teaching and those who are taught by conventional teaching; and d) investigating the significant difference in reading comprehension between the students with low self-concept who are taught by reciprocal teaching and those who are taught by conventional teaching. It was an experimental study by making use posttest-only control group with 2 x 2 factorial design. The population of the study was 240 tenth grade students of SMA Negeri 1 Gianyar in the academic year 2011/2012 wherein 80 students were chosen as the sample through Cluster Random Sampling. The research data were collected through a self-concept questionnaire and a reading comprehension test and were analyzed by using Two-Way Anova and Tukey test. The results discovered that, first, the students who were treated by reciprocal teaching obtained better reading comprehension than those who were treated by conventional teaching; second, there was an interactional effect between teaching methods and self-concept upon the studentsâ reading comprehension; third, the students with high-self concept obtained higherÂ reading comprehension when they were treated by reciprocal teaching than by conventional teaching; and fourth, the students with low self-concept attained higher reading comprehension when they were treated by conventional teaching than by reciprocal teaching. ABSTRAKMaharani, Anak Agung Putri (2012). Pengaruh Penggunaan Pengajaran Resiprokal dan Konsep Diri terhadap Pemahaman Membaca Siswa Kelas X di SMA Negeri 1 Gianyar. Tesis. Program Studi Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Pendidikan Ganesha.Tesis ini telah disetujui dan dikoreksi oleh:Pembimbing IÂ Â Â Â Â Â : Prof. Dr. A.A. Istri Ngurah Marhaeni, M. A.Pembimbing IIÂ Â Â : Dra. Luh Putu Artini, M.A. Ph.D.Kata Kunci: pemahaman membaca, pengajaran resiprokal, konsep diriPenelitian ini bertujuan untuk: a) mengetahui perbedaan signifikan pada pemahaman membaca di antara siswa yang diajar dengan pengajaran resiprokal dan siswa yang diajar dengan pengajaran konvensional; b) mengetahui efek interaksi yang terjadi di antara pengajaran resiprokal dan konvensional dengan konsep diri terhadap pemahaman membaca siswa; c) mengetahui perbedaan signifikan pada pemahaman membaca di antara siswa berkonsep diri tinggi yang mengikuti pengajaran resiprokal dan yang mengikuti pengajaran konvensional; dan d) mengetahui perbedaan signifikan pada pemahaman membaca siswa berkonsep diri rendah yang mengikuti pengajaran resiprokal dan yang mengikuti pengajaran konvensional. Studi eksperimen ini menggunakan rancangan penelitian posttest-only control group design dengan faktorial 2x2. Populasi penelitian berjumlah 240 siswa kelas X di SMA Negeri 1 Gianyar pada tahun ajaran 2011/2012 yang mana 80 siswa dipilih sebagai sampel dengan penyampelan acak cluster. Data penelitian dikumpulkan dengan menggunakan kuesioner konsep diri serta tes pemahaman membaca dan kemudian dianalisis menggunakan Anova dua jalur yang diikuti dengan tes Tukey. Adapun temuan-temuan penelitian ini yaitu: pertama, siswa yang mengikuti pengajaran resiprokal meraih pemahaman membaca yang lebih baik daripada siswa yang mengikuti pengajaran konvensional; kedua, terdapat efek interaksi di antara pengajaran resiprokal dan pengajaran konvensional dengan konsep diri terhadap pemahaman membaca siswa; ketiga, siswa berkonsep diri tinggi yang diajar dengan pengajaran resiprokal meraih pemahaman membaca yang lebih baik daripada siswa yang diajar dengan pengajaran konvensional; dan keempat, siswa berkonsep diri rendah yang diajar dengan pengajaran konvensional meraih pemahaman membaca yang lebih baik daripada siswa yang diajar dengan pengajaran resiprokal.